Radix entomolaris: Endodontic challenges and management in a mandibular first molar: A case series - Jain, Muskan; Pandey, Dr.Pragya; Yadav, Rakesh Kumar Yadav; Verma, Promila Verma; Bharti, Ramesh (Indian Journal of Case Reports, 2026)
Radix entomolaris (RE) is a rare anatomical variation in mandibular molars characterized by the presence of an additional distolingual root. Its detection and management present unique endodontic challenges, particularly in retreatment cases. This series presents four clinical cases involving mandibular first molars with RE. In the first case, the RE was discovered during access cavity preparation of a symptomatic tooth. In the second case, a missed radix canal resulted in post-treatment complications. In the third and fourth cases, a re-root canal treatment was carried out on a radix case to promote healing of a periapical lesion. The use of angled radiographs, magnification, and cone-beam computed tomography enabled accurate diagnosis and treatment. These cases underscore the importance of anatomical awareness and the use of advanced tools in achieving successful endodontic outcomes.